The Relationship between Mother’s Knowledge and Participation in the Use of Intrauterine Device Contraception at Jombang Health Center - Gempi Tri Sumini; Siti Nur Farida (Journal of Global Research in Public Health, 2020)
Contraception is a means of inhibiting the meeting of sperm and ovum so as not to meet and fertilization does not occur. The business is able to last a short or long time, and this business can be done with a variety of businesses, instruments and medicines. Based on data from the population in the Jombang District there are quantity of productive age assistants aged 20-35 years as many as 2,476 people. The purpose of the study is known forfind out whether there is a relationship between maternal knowledge and participation in intrauterine device use in the Jombang health center. This research is a type of primary research. According to the type of data including quantitative research this research method is Observation of cross sectional research. Population of women aged 20-35 years old and married in the Jombang Community Health Center area. A sample of some women aged 20-35 years old and married in the Jombang Community Health Center activity area was 248. The variables were knowledge of mothers aged 20-35 years, participation in the use of IUD contraception. Research results Based on the Spearman Rank test results that can be seen from Nonparametric correlations using SPSS 16, the P value of 0.001 was obtained, where the results were lower than the α = 0.05. This incident proves that Hodita was rejected, so there was a relationship.The Correlation coefficient is 0.553. So strengthThe relationship between knowledge of mothers aged 20-35 years about IUD contraception with participation in the use of IUD contraception is moderate